Tick control prevents carcass condemnations in lambs caused by Anaplasma ovis - Héctor Ruiz; Delia Lacasta; Sergio Villanueva-Saz; José María González; Aurora Ortín; Juan José Ramos; Alfredo Ángel Benito; Agustín Estrada-Peña; Antonio Fernández; Marina Pomar; Marta Ruiz de Arcaute (Veterinary Research Communications, 2024)
Ovine anaplasmosis is causing relevant economic losses in Spain due to icteric carcass condemnation in lambs. Anaplasma ovis infection occurs through grazing sheep that transfer ticks to their offspring. This study compared the efficacy of deltamethrin and cypermethrin pour-on treatments for tick control. A total of 250 PCR A. ovis -positive ewes and their offspring were divided into 5 groups. Group A (50 ewes/50 lambs) was kept as an untreated control group. In groups B (50/50) and C (45/93), the lambs were treated with deltamethrin pour-on and cypermethrin pour-on , respectively, one week after birth. In groups D (50/75) and E (51/68), the ewes were treated with cypermethrin pour-on and deltamethrin pour-on one week before the estimated parturition. External parasite assessment and A. ovis PCR were conducted before treatment and at 21 and 42 days post-treatment. Ewes were checked weekly for tick-detection until weaning. Lamb carcasses were examined at the slaughterhouse. Riphicephalus sanguineus sensu lato ticks were found in ewes throughout the study, with only one tick found in a control group lamb. Three lambs tested positive for A. ovis during the trial, with one condemnation at the abattoir due to jaundice. However, no significant differences were observed between treatment groups. Overall, a significant decrease in infected animals and condemned carcasses was observed compared to previous years, suggesting that deltamethrin and cypermethrin prevent A. ovis transmission from dams to lambs. Further studies are needed to confirm synthetic pyrethroids’ effectiveness in controlling tick infestation and averting A. ovis transmission to lambs.